Development of data-driven constitutive models for aerospace materials - Tasdemir, B (2023)
This study presents novel techniques to develop data-driven constitutive models. The adoption of data-based machine learning-driven models obtained from mechanical loading experiments allows for the accurate and computationally efficient prediction of the mechanical behaviour of materials eliminating the need for theoretical assumptions and potential constraints associated with traditional models.